2018
DOI: 10.1371/journal.pone.0194672
|View full text |Cite
|
Sign up to set email alerts
|

The first mitochondrial genomes for Pyralinae (Pyralidae) and Glaphyriinae (Crambidae), with phylogenetic implications of Pyraloidea

Abstract: In the present study, we report five complete and one nearly complete mitochondrial genomes of the Pyraloidea including the first representatives from the Pyralinae (Pyralidae) and Glaphyriinae (Crambidae). We also conduct a comparative analysis of mitogenomic features of this group. Our results show that Pyraloidea mitogenomes evolved under a common trend found in lepidopteran mitogenomes and share several typical genomic characters. The extra conserved blocks are identified in the Pyraloidea control region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 34 publications
13
20
0
Order By: Relevance
“…The mitogenome of C. exigua was a closed-circular molecule of 15,262 in length ( Table 1 ), which was within the range observed in the sequenced other Pyraloidea mitogenomes available with the size ranging from 15,110 bp in Maruca testulalis ( Zou et al 2016 ) to 15,594 bp in Ephestia kuehniella ( Zhu et al 2018 ). Annotation of the C. exigua mitogenome indicated that the structure and orientation of the 13 PCGs, 22 tRNA genes, 2 rRNA genes, and a noncoding region (A+T-rich control region) were typical of and similar to the other closely related pyraloid species ( Yang et al 2018 , Zhu et al 2018 ). Nine PCGs ( nad2 , nad3 , nad6 , cox1-3 , atp6 , atp8 , cytb ), 14 tRNAs, and the control region were located on the major J-strand.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The mitogenome of C. exigua was a closed-circular molecule of 15,262 in length ( Table 1 ), which was within the range observed in the sequenced other Pyraloidea mitogenomes available with the size ranging from 15,110 bp in Maruca testulalis ( Zou et al 2016 ) to 15,594 bp in Ephestia kuehniella ( Zhu et al 2018 ). Annotation of the C. exigua mitogenome indicated that the structure and orientation of the 13 PCGs, 22 tRNA genes, 2 rRNA genes, and a noncoding region (A+T-rich control region) were typical of and similar to the other closely related pyraloid species ( Yang et al 2018 , Zhu et al 2018 ). Nine PCGs ( nad2 , nad3 , nad6 , cox1-3 , atp6 , atp8 , cytb ), 14 tRNAs, and the control region were located on the major J-strand.…”
Section: Resultssupporting
confidence: 70%
“…Similar to other pyraloid species, the C. exigua mitogenome nucleotide composition was bias toward adenine and thymine (accounting for 81.6%: A = 40.5%, T = 41.1%, C = 10.9% G = 7.5%) ( Yang et al 2018 , Zhu et al 2018 ). The nucleotide bias was also reflected in the codon usage.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…In contrast, the trnI and trnH indicate relatively higher nucleotide substitutions. These results indicate that the tRNAs are relatively conserved which is similar to other Pyraloidea[55].…”
supporting
confidence: 68%